EFEKTIVITAS INTERNET OF THINGS (IOT) PADA SEKTOR PERTANIAN - Junaidi, Junaidi; Ramadhani, Kamal (JURNAL TEKNISI, 2024)
Abstract: Internet of Things (IoT) is a technology designed to make things easier for us by enabling connections with various devices via the internet. With IoT, daily work becomes easier and more efficient. This article is structured to identify the various benefits of IoT in the agricultural sector. The agricultural sector has an important role in the Indonesian economy with various commodities such as rice, palm oil, rubber, pepper, coffee, tea and others. IoT has great potential to transform the agricultural sector to become more productive, sustainable and ready to face future challenges. The result of writing this article is to provide an overview of the use of IoT in agriculture which can help farmers increase the yield and quality of their agriculture. Keywords: Internet of Things; Agriculture; Technology. Abstrak: Internet of Things (IoT) merupakan teknologi yang dirancang untuk memudahkan kita dengan memungkinkan koneksi dengan berbagai perangkat melalui internet. Dengan IoT, pekerjaan sehari-hari menjadi lebih mudah dan efisien. Artikel ini disusun untuk mengidentifikasi beragam manfaat IoT dalam sektor pertanian. Sektor pertanian memiliki peran penting dalam perekonomian Indonesia dengan berbagai komoditas seperti padi, kelapa sawit, karet, lada, kopi, teh, dan lainnya. IoT memiliki potensi besar untuk mengubah sektor pertanian menjadi lebih produktif, berkelanjutan, dan siap menghadapi tantangan di masa depan. Hasil dari penulisan artikel ini adalah memberikan gambaran tentang pemanfaatan IoT dalam pertanian yang dapat membantu petani meningkatkan hasil dan kualitas pertanian mereka. Kata kunci: Internet of Things; Pertanian; Teknologi.